Efficiency Comparaison and Evaluation between Two ETL Extraction Tools - Abdellah Amine; Rachid Ait Daoud; Belaid Bouikhalene (Institute of Advanced Engineering and Science, 2016)
In the prospects of making an array of onboard decision support in a public university, we present a comparison between two ETL extraction tools from a production database containing student information.For the implementation we use Pentaho and Sql Server tools and we illustrate the application on the case of Sultan Moulay Slimane University inBeniMellal, Morocco.